Hybrid Inhibitors of DNA Gyrase A and B: Design, Synthesis and Evaluation - Martina Durcik; Žiga Skok; Janez Ilaš; Nace Zidar; Anamarija Zega; Petra Éva Szili; Gábor Draskovits; Tamás Révész; Danijel Kikelj; Akos Nyerges; Csaba Pál; Lucija Peterlin Mašič; et al. (MDPI AG, 2020)
The discovery of multi-targeting ligands of bacterial enzymes is an important strategy to combat rapidly spreading antimicrobial resistance. Bacterial DNA gyrase and topoisomerase IV are validated targets for the development of antibiotics. They can be inhibited at their catalytic sites or at their ATP binding sites. Here we present the design of new hybrids between the catalytic inhibitor ciprofloxacin and ATP-competitive inhibitors that show low nanomolar inhibition of DNA gyrase and antibacterial activity against Gram-negative pathogens. The most potent hybrid 3a has MICs of 0.5 µg/mL against Klebsiella pneumoniae, 4 µg/mL against Enterobacter cloacae, and 2 µg/mL against Escherichia coli. In addition, inhibition of mutant E. coli strains shows that these hybrid inhibitors interact with both subunits of DNA gyrase (GyrA, GyrB), and that binding to both of these sites contributes to their antibacterial activity.